Hello
Iv been told to rearrang the following equation:
n^{m+1} = (C^{m+1} x (V - U)^{m+1}) / (Q x D)^{m+1}
so that:
n^{m+1} x Q x D = ??????
every time iv done it iv been told i got it wrong.
Can some one please help me.
I suspect you really want n x Q x D= rather than the n+1 power of r.
From $\displaystyle n^{m+1}= \frac{C^{m+1}(V- U)^{m+1}}{(QD)^{m+1}}$, you can write it as $\displaystyle n^{m+1}= \left(\frac{C(V- U)}{QD}\right)^{m+1}$
and take the n+1 root to get $\displaystyle n=\frac{C(V- U)}{QD}$ and then multiply both sides by QD:
$\displaystyle nQD= C(V- U)$